Investment Behaviour of Individual Investors of Pakistan Stock Market with Moderating Role of Financial Literacy - SABIR, DR. SAEED AHMAD; JAVED, TASAWAR; KHAN, SHAHBAZ ALI; JAVED, MUHAMMAD ZAHID (The journal of contemporary issues in business and government, 2021)
The purpose of this study is to examine the determinants of investors’ behaviour in the Pakistan stock market with the moderating role of financial literacy. The study also explains the mediating mechanism between the attitude of investment, religiosity, social influence and investment behaviour in stocks. This study used quantitative method to test the hypotheses. The data was collected by using survey approach and self-administrative questionnaire. The data was collected from 250 stock investors through convenience sampling. This study utilized Partial Least Squares structural equation modelling method (PLS-SEM) to test modelled hypothesis and used the Smart PLS version 2.0 to conduct the analysis. This study found that social influence and religiosity influence investment intention while religiosity doesn’t affect investment behaviour. This study also indicates that relationship of investment intention and investment behaviour of individual investors in stock market was significantly moderated by financial literacy. Moreover, results indicate that intentions to investment significantly mediate between the religiosity and investment in stock. Similarly, intentions to investment significantly mediate between social influence and investment in stock. However, intention to investment doesn’t significantly mediate between attitude toward investment and investment behaviour in stock. This study extends the existing literature, specifically in a Pakistan context and helps the policymaker to develop policies to increase investment in the stock market.